2018
DOI: 10.1111/jcmm.13749
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamin‐related protein 1‐mediated mitochondrial fission contributes to IR‐783‐induced apoptosis in human breast cancer cells

Abstract: IR‐783 is a kind of heptamethine cyanine dye that exhibits imaging, cancer targeting and anticancer properties. A previous study reported that its imaging and targeting properties were related to mitochondria. However, the molecular mechanism behind the anticancer activity of IR‐783 has not been well demonstrated. In this study, we showed that IR‐783 inhibits cell viability and induces mitochondrial apoptosis in human breast cancer cells. Exposure of MDA‐MB‐231 cells to IR‐783 resulted in the loss of mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…During recent years, a growing body of evidence has suggested the close links between mitochondrial fission and fusion dysfunction and cancers . Dysregulated expressions of DRP1 and DRP1 and MFN2 have been observed in several types of cancer such as liver, breast, and lung cancers. However, the expression patterns and biological effects of these mitochondrial fission and fusion regulators in PC remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, a growing body of evidence has suggested the close links between mitochondrial fission and fusion dysfunction and cancers . Dysregulated expressions of DRP1 and DRP1 and MFN2 have been observed in several types of cancer such as liver, breast, and lung cancers. However, the expression patterns and biological effects of these mitochondrial fission and fusion regulators in PC remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Mitochondrial fusion and fission contribute to these morphologic changes and are often dysregulated under pathological conditions, including cancers. 18,19,25,28,51 Most studies of cancer-related mitochondrial dynamics focus on their function in apoptosis, [52][53][54] and elevated mitochondrial fission has been linked to impaired oxygen consumption in cancer cells. 18,[55][56][57] However, it is not clear whether mitochondrial dynamics regulate metabolic alterations in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…25 High expression of DRP1 in cancer may be a potential target for cancer treatment. 4,5,22,24,[26][27][28] Mitochondrial division inhibitor 1 (mdivi-1) is an efficacious inhibitor of mitochondrial division in yeast and was identified from a chemical screen for compounds that alter mitochondrial morphology. 29 Not surprisingly, mdivi-1 has been widely used as a mitochondrial fusion inducer.…”
mentioning
confidence: 99%
“…85 Also cryptolepine and IR-783 inhibited tumor cell growth and at the same time led to dose-dependent OPA1 protein loss. 251,252 Accordingly, rat neuroblastoma cells after cisplatin treatment and successive long-term recovery showed increased OPA1 protein levels and more fused mitochondria. 253 Another study demonstrated p53-dependent OPA1 cleavage in cisplatin treated human cervical and ovarian cancer cell lines, 169 which suggests that chemotherapies exert their cytotoxic effects through OMA1mediated OPA1 cleavage in a p53-dependent manner.…”
Section: Prohibitinmentioning
confidence: 99%
“…For example, one study found that sorafenib induced rapid mitochondrial fragmentation, cytochrome c release and apoptosis in hepatocellular carcinoma cells, which involved loss of OPA1 and which was further amplified by OPA1 knock‐down . Also cryptolepine and IR‐783 inhibited tumor cell growth and at the same time led to dose‐dependent OPA1 protein loss . Accordingly, rat neuroblastoma cells after cisplatin treatment and successive long‐term recovery showed increased OPA1 protein levels and more fused mitochondria .…”
Section: Control By Tumor Proteinsmentioning
confidence: 99%